استقلالــــــیة الـــــــمدقق الــــــداخــلي ودوره في تــــضییق فــــــجوة الـــــتوقعات - دراسة تطبیقیة لمجموعة من شركات المساھمة العاملة بولایتي غردایة، ورقلة -الجزائر - زقيب, خيرة (جامعة الوادي - University of Eloued, 2015)
This study aims to identify the reality of the independence of the internal auditor and its effective role in narrowing the expectations gap of Algerian contributesfirms toWillaya « Ghardaia and Ouargla ».By reflecting the role of the internal auditor and the extent of its independence in reducing the gaps between the users of financial statements and the reports of the internal auditor.It was done through conduct factto the opinions of the respondents were prepared questionnaire distributed to specific sample at the level of joint stock companies under study consisted in: (Head of internal audit Department, internal auditor, chairman of the audit Committee, a member of the audit Committee, accountant, assistant accountant), the 09 joint-stock companies in addition to its branches the study Mahal has been distributed (62) questionnaire and recovered all the questionnaires were excluded one questionnaire study relied on the approach and descriptive method of analysis in the theoretical side of the practical side has been relying on the case study method and methods of descriptive statistics of the arithmetic mean and standard deviation, correlation coefficient to test hypotheses and to answer the study questions wereOlvakronbach coefficient calculation to determine the validity and reliability of the questionnaire.
The independence of the internal auditor and itsrole in narrowing the gap expectations – Empirical Study of a group of state companies to contribute to the working Ghardaia, Ouargla- Algeria
مقال
Keywords: Audit, Internal Auditor, expectation gap , independence, objectivity